Synergistic antibacterial effect of hydroxyl radicals generated by the combination of hypochlorous acid and UV irradiation - Hwa Yong Lee; Han Bit Lee; Younghee Kim (PLoS ONE, 2025)
Livestock farms are at risk of exposure to various environmental pollutants, particularly airborne viruses that can cause infectious diseases. Hydroxyl radicals (•OH) are well-known for their strong bactericidal and virucidal properties and are widely applied in disinfection processes. However, their efficacy is significantly diminished in the presence of organic substances. This study investigated the bactericidal effects of hydroxyl radicals generated from hypochlorous acid (HOCl) under UV irradiation and evaluated their resistance to quenching by airborne organic matter. Rose Bengal (RNO) dye was used as a probe to detect •OH radical generation, while yeast extract served as a representative organic contaminant. RNO bleaching efficiency increased in a concentration-dependent manner under UV irradiation, confirming the formation of hydroxyl radicals. However, in the presence of yeast extract, this bleaching effect was drastically reduced, indicating that organic compounds can interfere with radical activity. The bactericidal effects of UV light and HOCl were independently evaluated using Salmonella as a model organism. The presence of organic matter significantly reduced the bactericidal efficacy of both UV and HOCl treatments when applied separately. In contrast, combined exposure to HOCl and UV irradiation demonstrated a 10% increase in bacterial reduction and halved the required exposure time, regardless of HOCl concentration. These findings highlight the synergistic bactericidal potential of HOCl and UV irradiation and support their applicability in airborne bacterial disinfection under realistic environmental conditions.